Recovery of lipase from Burkholderia sp.using aqueous two-phase systems - Show, Pau Loke (2012)
Conventional recovery methods for lipase are tedious and require several rounds of recovery steps. Therefore, the development of a cost-effective and recyclable protocol for the recovery of lipase is essential. Aqueous two-phase system (ATPS) can be used as an attractive alternative for the recovery of lipase from complex feedstock. This research is focused on the design of an ATPS protocol as a simplified and rapid recovery technique for the microbial lipase of Burkholderia sp. ST8. A multifactor experimental design based on a ‘change-one-factor-at-a-time’ approach was employed to study the effects of lipase production. A high lipase activity was achieved at a 250 rpm agitation speed for 36 hours of fermentation time in a cultivation medium containing 0.1 % (v/v) of Tween 80, 0.3 % (w/v) of nutrient broth and 0.1 % (w/v) of CaCl2 at a pH of 9 with a volume ratio of 20:80 of medium volume to free volume of the flask which resulted in a high average production of 48.3 U/mL. Three different novel techniques for the direct recovery of lipase based on sustainable ATPS have been developed. The recycling concept in the system is based on the principals of green chemistry, with good efficiency and economic viability. The first novel method is a recycling hydrophilic organic solvent/inorganic salt aqueous two-phase flotation (ATPF) system, which integrates solvent sublation (SS) and aqueous two-phase extraction (ATPE) in the recovery of lipase from fermentation broth. A purification factor of 14 and a lipase yield of 99 % were achieved in the optimized ATPF system with recovery of alcohol and salt are 70% and 61 %, respectively. The second and third lipase recovery techniques were explored by using a recyclable temperature-induced polymer, an ethylene oxidepropylene oxide (EOPO) polymer in an ATPF system as well as an ATPS. As for the second method, a recycling EOPO/ammonium sulphateATPF was developed for the recovery of lipase from fermentation broth. Under the optimal conditions, the average yield and purification factor were 98.5 % and 15, respectively. It was also demonstrated that EOPO and salt was recovered up to 91 % and 75 % in the ATPF system. Direct lipase recovery using recycling an EOPO/potassium phosphate ATPS was studied as the third protocol in this thesis. The average purification factor of lipase and the yield obtained from four successive purifications were 15.3 and 99.1 %, respectively. There was no significant difference in using fresh or recycled chemicals in these three novel methods based on ATPS. The choice of method in lipase recovery based on ATPS is subjected to the requirement of the purity and cost of the system. Hence, the simplicity and effectiveness of these three lipase recovery methods based on sustainable ATPS were proven in this study. Lastly, an extractive fermentation technique was employed using a thermoseparating reagent to form a two-phase system for simultaneous cell cultivation and downstream processing. A 10 % (w/w) solution of EOPO with a molecular mass of 3900 g/mol and a pH of 8.5, a 200 rpm speed, and 30 °C were selected as the optimal conditions for lipase production (55 U/ml). Repetitive batch fermentation was performed by continuous replacement of the top phase every 24 hours, which resulted in an average cell growth mass of 4.8 g/L for 10 extractive batches over 240 hours. The dry cell mass in the bioreactor was 22 % higher than that in the flasks. Burkholderia sp. ST8 lipase was successfully produced and recovered by using thermoseparating reagents in a single step - extractive fermentation.